Two bathyal hydroids (Hydrozoa: Leptothecata) from the Southwest Indian Ocean - Watson, Jeanette E. (Zootaxa, 2017)
Two species of hydroids were recovered from a mooring rope and experimentally deployed whale bone attached to an underwater transponder buoy at a depth of 732 m on the Coral Seamount on the Southwest Indian Ocean Ridge (41° 22.31’S, 54° 57’E) in the Southern Indian Ocean. The material was collected approximately 1,500 km south south-east of Madagascar during Voyage JC066 of the British Royal Research Ship R.R.S. James Cook on 20/11/2011. Hydroids were collected from the mooring rope and whale bone on board the ship after underwater retrieval by ROV.